On the cation–π capabilities of small all sp2‐carbon host structures. Evaluation of [6.8]3cyclacene from relativistic DFT calculations. Issue 4 (11th October 2018) - Ortolan, Alexandre O.; Charistos, Nicholas D.; Guajardo‐Maturana, Raul; Ulloa, Carolina Olea; Caramori, Giovanni F.; Parreira, Renato L. T.; Muñoz‐Castro, Alvaro
Abstract: Cation–π interactions are noncovalent forces with essential roles in the stability of protein structures, molecular recognition, and host–guest chemistry. In this work, we discuss the formation of cation–π complexes involving one of the smallest characterized nanobelts to date, given [6.8]3 cyclacene, by using relativistic DFT‐D calculations. Such nanobelt exhibits a noteworthy all‐sp 2 carbon backbone, leading to a rigid and confined host framework. Our results reveal that the inclusion of representative cations, such as Ag + and Sn 2+, appears to be plausible, revealing that it is feasible to obtain these compounds experimentally. Such systems involves two contrasting coordination modes, where the Ag + cation remains coordinated in the upper face of the nanobelt, whereas the Sn 2+ is able to be located at the center of the structure. In addition, the coordination of isoelectronic Cd 2+ and In + was also discussed. Moreover, the bonding characteristics of the resulting cation–π interaction show that the π‐orbitals from the nanobelt1 are able to moderate the charge transfer, according to the selected cation, which can be seen as an interesting strategy to tune the amount of charge of the π‐backbone in nanobelts. We envisage that the use of more rigid host in the formation of cation–π interactions will be beneficial to gain a better understanding about the metal coordination and also to tune the capabilities of related nanobelts or nanotubes sections. Abstract : The formation of cation–π complexes involving one of the smallest characterized nanobelts to date, [6.8]3 cyclacene, is evaluated via relativistic DFT‐D calculations. It is shown that the rigid all‐sp 2 carbon backbone leads to a rigid and confined host framework, allowing the inclusion of representative cations such as Ag + and Sn 2+ . This is beneficial to gain a better understanding about the metal coordination and also to tune the capabilities of related nanobelts or nanotubes sections.